Hashimoto’s Thyroiditis and Graves’ Disease in One Patient: The Extremes of Thyroid Dysfunction Associated with Interferon Treatment - R. H. Bishay; R. C. Y. Chen (Case Reports in Endocrinology, 2016)
Autoimmune thyroid disease associated with interferon therapy can manifest as destructive thyroiditis, Graves’ Hyperthyroidism, and autoimmune (often subclinical) hypothyroidism, the latter persisting in many patients. There are scare reports of a single patient developing extremes of autoimmune thyroid disease activated by the immunomodulatory effects of interferon. A 60-year-old man received 48 weeks of pegylated interferon and ribavirin therapy for chronic HCV. Six months into treatment, he reported fatigue, weight gain, and slowed cognition. Serum thyroid stimulating hormone (TSH) was 58.8 mIU/L [0.27–4.2], fT4 11.1 pmol/L [12–25], and fT3 4.2 pmol/L [2.5–6.0] with elevated anti-TPO (983 IU/mL [<35]) and anti-TG (733 U/mL [<80]) antibodies. He commenced thyroxine with initial clinical and biochemical resolution but developed symptoms of hyperthyroidism with weight loss and tremor 14 months later. Serum TSH was <0.02 mIU/L, fT4 54.3 pmol/L, and fT3 20.2 pmol/L, with an elevated TSH receptor (TRAb, 4.0 U/L [<1.0]), anti-TPO (1,163 IU/mL) and anti-TG (114 U/mL) antibodies. Technetium scan confirmed Graves’ Disease with bilateral diffuse increased tracer uptake (5.9% [0.5–3.5%]). The patient commenced carbimazole therapy for 6 months. Treatment was ceased following spontaneous clinical and biochemical remission (TSH 3.84 mIU/L, fT4 17pmol/L, fT3 4.5 pmol/L, and TRAb <1 U/L). This raises the need to monitor thyroid function closely in patients both during and following completion of interferon treatment.